Transformation Of Traditional Tafsir To Modern Perspective Of Fazlur Rahman's Hermeneutics - Nurcahyati, Nurcahyati; Haqiqi, Haqiqi (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
This article examines the transformation of tafsir from traditional to modern in the perspective of Fazlur Rahman's hermeneutics. This research was conducted using qualitative methodology with hermeneutic analysis to understand the mufassir's efforts in answering the challenges of the times in a more contextual and relevant way. The traditional textual approach is now replaced by a more unified hermeneutic method, combining social, historical and linguistic analysis. This allows Qur'anic interpretation to deepen meanings that are not only appropriate to the context of the past, but also relevant to modern social, political and cultural realities. The development of globalization and modernity has had a significant impact on the dynamics of tafsir, with modern mufassirs applying adaptive methods to address social issues. However, this transformation faces the challenge of maintaining a balance between innovation and respect for tradition and the authority of the sacred text. The interim conclusion of the study shows that changes in tafsir not only enrich the intellectual horizons of Islam, but also play an important role in developing an understanding and practice of the Qur'an that is more relevant to the context of modern society.